2016
DOI: 10.1177/1420326x16663289
|View full text |Cite
|
Sign up to set email alerts
|

How are characteristics of urban green space related to levels of physical activity: Examining the links

Abstract: This study investigates the associations between characteristics of urban green spaces and frequency and duration of self-reported physical activity in the city of Aydın, Turkey. Data were collected through a survey with 420 participants. We analysed the associations between characteristics of urban green spaces and frequency and duration of general population' physical activity and physical activity of physically active people with multivariate linear regression while controlling for sex, age, marital status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 49 publications
(121 reference statements)
1
35
0
Order By: Relevance
“…Lastly, some studies found that some characteristics of green space are associated with PA (Akpinar & Cankurt, 2016). It is important to note that, each type of green has different characteristics and human perception of landscapes is found to be associated with health and stress reduction (Ulrich, 1984;Ulrich et al, 1991), increased neighborhood satisfaction (Kaplan, 2001),and better restoration (Van den Berg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, some studies found that some characteristics of green space are associated with PA (Akpinar & Cankurt, 2016). It is important to note that, each type of green has different characteristics and human perception of landscapes is found to be associated with health and stress reduction (Ulrich, 1984;Ulrich et al, 1991), increased neighborhood satisfaction (Kaplan, 2001),and better restoration (Van den Berg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is because the physical features in a recreational park can provide opportunities to attract users to do activities, thus will make the place vibrant in use due to increasing numbers of visitor. It is found that attributes such as general population (carrying capacity), short distance, many trees, open lawn, exercise equipment, soccer and basketball fields, and picnic areas are features that attract users to use parks and green spaces (Akpinar and Cankurt, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers in many countries in the world have provided various evidence on the benefits of recreational parks (e.g. studies by Akpinar and Cankurt, 2016;Zainol and Au-Yong, 2016;Nasir, Ahmad and Ahmed, 2013;McCormack et Department of Landscape Architecture, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia (IIUM), Kuala Lumpur, MALAYSIA al., 2010). Regrettably, there are also negative perceptions regarding use of recreational parks in urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is no longer a groundbreaking statement that urban green spaces (UGS) can improve people's well-being (Kothencz et al 2017) and public health (Richardson et al 2013), enhance social interaction, and provide the space for leisure or recreational activities (see Akpinar and Cankurt 2017). In densely populated areas, UGS can reduce air pollution and improve climate, contribute to keeping ecological balance, promote biodiversity, reduce noise, and improve urban economy (Kothencz et al 2017;Lee and Maheswaran 2011).…”
Section: Introductionmentioning
confidence: 99%